2005
DOI: 10.1007/s00216-005-3385-z
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of Cd-bound phytochelatins by Phaeodactylum tricornutum and their speciation by size-exclusion chromatography and ion-pair chromatography coupled to ICP–MS

Abstract: Cd-bound phytochelatins (Cd-PCs) have been synthesised by incubation of Phaeodactylum tricornutum cell cultures with Cd and purified by size-exclusion chromatography-UV-Vis. These complexes, which were identified in previous work, have now been used as model substances to develop and optimise ion-pair chromatography (IPC) coupled to inductively coupled plasma-mass spectrometry (ICP-MS) for analysis of Cd-PCs. Subsequent analysis of samples taken from Silene vulgaris plants cultivated under heavy metal stress c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…10,20 Apparently, Cd-PC complexes are believed to be labilized to a great extent in the vacuoles 8 since they are very unstable under those acidic conditions (contrary to the As complexes) and this fact could explain why only minor traces of this compound can be detected. 15…”
Section: Analysis Of the Brassica Extracts By Esi-q-tofmentioning
confidence: 99%
See 1 more Smart Citation
“…10,20 Apparently, Cd-PC complexes are believed to be labilized to a great extent in the vacuoles 8 since they are very unstable under those acidic conditions (contrary to the As complexes) and this fact could explain why only minor traces of this compound can be detected. 15…”
Section: Analysis Of the Brassica Extracts By Esi-q-tofmentioning
confidence: 99%
“…In this regard, the use of mass spectrometric techniques can be extremely useful for detecting and characterizing the chemical structures of these complexes in plant tissues. In fact, inductively coupled plasma mass spectrometry (ICP-MS) has proved to be an extraordinary tool for selective detection of As 12,13 and Cd 14,15 containing species, previously separated in a chromatographic system, in plant tissues. Complementary to element selective detection by ICP-MS, electrospray ionization mass spectrometry (ESI-MS) has become the technique of choice for elucidating the structure of several of these organometallic/metalloid complexes.…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge of PC n complexation becomes very important because of the extended use of plants and other organisms for bioremediation of heavy-metal contaminated soils and waters [1]. A variety of techniques have been used for the analysis and identification of the different metal-PC n complexes: UV-vis spectroscopy [2], size-exclusion chromatography [3], Electrospray Ionization Mass Spectrometry (ESI-MS) [4 -7] and electroanalytical techniques [8 -10].…”
Section: Introductionmentioning
confidence: 99%
“…The cadmium-containing fractions are therefore collected and the phytochelatins are further separated by a reversed-phase highperformance liquid chromatography (RP-HPLC) with pre-column or post-column derivatization using UV-vis or fluorescence detection. Loreti et al recently showed this second separation coupled to ICP-MS [25]. The separation conditions used in the RP-HPLC, as well as the derivatization protocol used in these techniques, require an acidification step wherein the cadmium-phytochelatin complexes are dissociated and are rather used to characterize the apo-phytochelatins.…”
Section: Introductionmentioning
confidence: 99%